2022
DOI: 10.3389/fstro.2022.1010928
|View full text |Cite|
|
Sign up to set email alerts
|

Adenosine A1R/A3R agonist AST-004 reduces brain infarction in mouse and rat models of acute ischemic stroke

Abstract: Acute ischemic stroke (AIS) is the second leading cause of death globally. No Food and Drug Administration (FDA) approved therapies exist that target cerebroprotection following stroke. Our group recently reported significant cerebroprotection with the adenosine A1/A3 receptor agonist, AST-004, in a transient stroke model in non-human primates (NHP) and in a preclinical mouse model of traumatic brain injury (TBI). However, the specific receptor pathway activated was only inferred based on in vitro binding stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…1 Preclinical efficacy of this agent was demonstrated in many preclinical rodent models of stroke and in a translationally relevant primate model of transient middle cerebral artery occlusion using a protocol that emulated clinical study timelines as described in the HERMES (Highly Effective Reperfusion Using Multiple Endovascular Devices) meta-analysis. 2,3 In that study, a reduction in mean values of infarct volumes of up to 45% was reported following AST-004 administration. AST-004 has completed human phase I clinical safety trials in preparation for further development in phase II proof of concept studies in patients with stroke.…”
mentioning
confidence: 84%
“…1 Preclinical efficacy of this agent was demonstrated in many preclinical rodent models of stroke and in a translationally relevant primate model of transient middle cerebral artery occlusion using a protocol that emulated clinical study timelines as described in the HERMES (Highly Effective Reperfusion Using Multiple Endovascular Devices) meta-analysis. 2,3 In that study, a reduction in mean values of infarct volumes of up to 45% was reported following AST-004 administration. AST-004 has completed human phase I clinical safety trials in preparation for further development in phase II proof of concept studies in patients with stroke.…”
mentioning
confidence: 84%